Azoimine Chelated Ruthenium(II)- and Osmium(II)-Carbonyl Complex Catalyzed Alcohol Oxidation Reaction - Sinha, Chittaranjan (Current Organocatalysis, 2019)
Arylazoimidazole brings azoimine (-N=N-C=N-) chelating N(azo), N(imine) (abbreviated - N, N/) centres and forms Ru(II) and Os(II) carbonyl complexes. These complexes act as catalysts for the oxidation of alcohols to aldehydes/ketones by tertiary butyl hydro peroxide (ButOOH), hydrogen peroxide (H2O2) and N-methylmorpholine-N-oxide (NMO) as oxygen sources. Different substituted arylazoimidazoles such as 1-alkyl-2-(arylazo)imidazoles (RaaiR/), 1-alkyl-2-(naphthyl-α/β- azo)imidazoles (α/β-NaiR) and (1-alkyl-2-(o-thioalkyl)phenylazoimidazole, SRaaiNR/) are used to prepare Ru/Os-CO complexes. Ancillary ligands like hydride (H-), chloride (Cl-), triphenylphosphine (PPh3) are used to monitor the catalytic efficiency of the complexes. Aromatic and aliphatic alcohols like benzyl alcohol, 2-butanol, cyclopentanol, cyclohexanol, 1-phenylethanol, cinnamyl alcohol, diphenylmethanol, are oxidized to the corresponding benzaldehyde, 2-butanone, cyclopentanone, cyclohexanone, phenylacetone, cinamaldehyde, cyclopentanone, benzophenone, respectively. Different physicochemical analyses (FT-IR, UV-Vis, Mass, NMR) suggest that the complexes react with an oxidant to yield high valent ruthenium/osmium-oxo species (RuIV=O; OsIV=O), which is capable of transferring the oxygen atom to alcohols. GC analysis accounts that percentage conversion order is as follows : Cinnamyl alcohol > Cyclohexanol 1-Phenylethanol > Diphenylmethanol > Cyclopentanol > 2-Butanol > Benzyl alcohol. The oxidation efficiency of the oxidant follows the order : NMO > ButOOH > H2O2. RuII complexes are more potent catalysts than OsII complexes. Out of three series of RuII complexes, [RuCl(CO)(SMeaaiNEt)]ClO4 and [RuCl(CO)(SEtaaiNMe)]ClO4 showed highest catalytic efficiency amongst 32 catalysts.
Keywords: osmium